2006
DOI: 10.1016/j.freeradbiomed.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative signaling in renal epithelium: Critical role of cytosolic phospholipase A2 and p38SAPK

Abstract: Previous studies from this laboratory have demonstrated a critical role of cytosolic phospholipase A 2 (cPLA 2 ) and arachidonic acid in angiotensin II (Ang II) AT2 receptor-mediated signal transduction in renal epithelium. In primary proximal tubular epithelial cells exposed to hydrogen peroxide (H 2 O 2 ), both the selective cPLA 2 inhibitors and the cPLA 2 antisense oligonucleotides significantly attenuated H 2 O 2 -induced arachidonic acid liberation and activation of p38 SAPK , ERK1/2, and Akt1. This H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…These data suggest differences in AT2 receptor coupling in ARPE-19 cells. AT2 receptor could be specifically coupled to the cytosolic phospholipase A 2 (cPLA 2 ), as has been shown recently in renal mesangial and proximal tubular epithelium cells, and not to the PLC pathway (15). Therefore, selective up-or downregulation of only AT2 receptor transduction pathway remains a possibility to be investigated.…”
Section: Discussionmentioning
confidence: 98%
“…These data suggest differences in AT2 receptor coupling in ARPE-19 cells. AT2 receptor could be specifically coupled to the cytosolic phospholipase A 2 (cPLA 2 ), as has been shown recently in renal mesangial and proximal tubular epithelium cells, and not to the PLC pathway (15). Therefore, selective up-or downregulation of only AT2 receptor transduction pathway remains a possibility to be investigated.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that MAPKs itself may be an intracellular target of oxidative stress in the mouse ES cells that mediates, at least in part, the cell response to H 2 O 2 . Previously, H 2 O 2 was found to induce the release of arachidonic acid (AA) in other cell types, which could be attributed to the activation of p44/42 MAPKs, and the consequent phosphorylation and activation of cytosolic phospholipase A 2 (cPLA 2 ) [45]. These results showed that H 2 O 2 individually stimulated the phosphorylation of p44/42 MAPKs, and the release of AA by mouse ES cells.…”
Section: Discussionmentioning
confidence: 90%
“…We employed H 2 O 2 to initiate intracellular oxidative stress, as H 2 O 2 is involved in renal disease and is readily permeable to the plasma membrane [28]. A treatment dose of 0.75 m M H 2 O 2 was chosen according to preliminary studies (data not shown) and cell apoptosis was monitored over a period of up to 24 h after H 2 O 2 treatment.…”
Section: Resultsmentioning
confidence: 99%